2018
DOI: 10.1007/s00269-018-0985-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic theoretical study of [001] symmetric tilt grain boundaries in MgO from 0 to 120 GPa

Abstract: The properties of [001] symmetric tilt grain boundaries (STGBs) in magnesium oxide are investigated systematically with atomic-scale simulations. Their formation energies, atomic structures, and excess volumes are computed. STGBs are found to prefer a symmetric configuration, except for tilt angles larger than 67.4°, where the decomposition of the STGBs into ½[110] dislocations is preferred. Then, the effects of pressure are investigated from 30 up to 120 GPa, a pressure range relevant to the Earth's lower man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 51 publications
7
16
2
Order By: Relevance
“…The interfacial energy of 1.47 J m −2 at 1.23 GPa found in this study is very similar to the previous ab initio study of 1.51 J m −2 by Verma and Karki (LDA) and somewhat below that of 1.95 J m −2 found in the embedded cluster study of McKenna and Shluger. There is also a small discrepancy between this work and the pair potential study of Hirel et al (2018), who found an interfacial energy of 1.63 J m −2 . Despite the LDA functional Harris et al 1996;Yokoi and Yoshiya 2018) and previously thought to be the most stable structure at intermediate pressures.…”
Section: Migration Energy Barriercontrasting
confidence: 98%
See 3 more Smart Citations
“…The interfacial energy of 1.47 J m −2 at 1.23 GPa found in this study is very similar to the previous ab initio study of 1.51 J m −2 by Verma and Karki (LDA) and somewhat below that of 1.95 J m −2 found in the embedded cluster study of McKenna and Shluger. There is also a small discrepancy between this work and the pair potential study of Hirel et al (2018), who found an interfacial energy of 1.63 J m −2 . Despite the LDA functional Harris et al 1996;Yokoi and Yoshiya 2018) and previously thought to be the most stable structure at intermediate pressures.…”
Section: Migration Energy Barriercontrasting
confidence: 98%
“…Structure (c) is more compact than the previous structure (a), with a small shift in the GB plane allowing Mg-O bonds to form whilst reducing the volume of the interface. Finally, structure (d) stable at pressure > 100 GPa is the most stable high-pressure structure and is observed in this and previous work (Verma and Karki 2010;Harris et al 1996;Hirel et al 2018). It features a relative shift in atomic planes parallel to the interfacial axis of rotation, resulting in a structure containing dislocation pipes.…”
Section: Migration Energy Barriersupporting
confidence: 72%
See 2 more Smart Citations
“…However, as t′ and t″ are mostly controlled by temperature, the pressure effect should be very limited in the lithospheric mantle and the A-regime should always occur with depth increase. Regarding grain boundary complexion (e.g., Dillon & Harmer, 2008b), segregation between grain boundaries and the mineral lattice is pressure dependent (e.g., Hirel et al, 2018;Marquardt & Faul, 2018) since the grain boundary structure becomes less disordered, and denser with increasing confining pressure. Thus, grain boundary segregation should decrease with increasing pressure.…”
Section: Transport Of Ar In the Earth's Mantlementioning
confidence: 99%